PENGARUH IKATAN KEUANGAN, SOSIAL DAN STRUKTURAL TERHADAP LOYALITAS NASABAH PADA KSP BANGUN BERSAMA SEMARANG - Sabtarini Kusumaningsih; Titik Rianawati2 (BADAN PENERBIT STIEPARI PRESS, 2022)
The purpose of this study is to provide empirical evidence of the influence of the financial ties, social ties and structural bonding on customer loyalty at KSP Bangun Bersama. The analytical method used in this research is quantitative method with multiple regression testing by performing classical assumption test before getting the best research model. The variable in this study is a finacial bond, social bonding and structural bonding as independent variables and customer loyalty as the dependent variable. Data were collected by census method, the entire population od 65 respondents taken sample. The method of analysis using multiple linear regression. The results of this research are financial ties, social ties and structural bonding and significant positive effect on customer loyalty.